Ethnicisation, Marriage and Early Christian Identity: Critical Reflections on 1 Corinthians 7, 1 Peter 3 and Modern New Testament Scholarship* - Horrell, David G. (New Testament studies, 2016)
In the discipline of New Testament studies there are particular reasons for critical vigilance concerning the ways in which historical reconstructions can be shaped by a sense of both religious and ethnic or racial superiority. This risk applies specifically to the contrasting depictions of Judaism and Christianity, and it is notable that, despite the changing phases of scholarship, the tendency to replicate a dichotomy between an ethnically particular Judaism and a universal, open, trans-ethnic Christianity persists. As one facet of a critical consideration of this dichotomy, this essay considers two specific texts that contribute to the ethnicisation of early Christian identity: 1 Corinthians 7 and 1 Peter 3. In the former, Paul develops two principles that are significant in the ethnicisation process: endogamy as norm for the contraction of marriage (1 Cor 7.39) and the assumption that children with a Christian parent (even in a so-called mixed marriage') are part of the Christian community (1 Cor 7.14). The later household codes further develop this idea that the household is a place for the reproduction and generation of Christian identity. In 1 Pet 3.1-6, part of the letter's household code where mixed marriage is again an issue, two features of the text are of particular interest: its focus on a way of life' (anastrophē) and the connections drawn between conduct and ancestry. In both of these respects, 1 Peter seems to be constructing a form of group-identity that shares features in common with Jewish notions of group-belonging in the period. The ethnicising' features of these texts raise questions about any categorical contrast between Jewish ethnicity and Christian inclusive trans-ethnicity. Why then is such a depiction of the Christian achievement - which in many ways parallels depictions of modern Western political liberalism - so enduring and appealing within the discipline? It is suggested that the answer must be sought in the religious and ethnic or racial location of that scholarly tradition.